Microscopic geometrical structure analysis of 2D and 2.5D fabrics based on a simple predictive model. (29th October 2021) - Wang, Yang; Wang, Qiuhui; Yang, Jian
Abstract: The braided structure has a great influence on the properties of composites, and it is of great significance to predict and design the microscopic geometrical structure of fabric. In this paper, a simple model for predicting the yarn morphologies in 2D plain weave fabric and 2.5D shallow-cross bending fabric is established. Compared with the test results, this predictive model has relatively high prediction accuracy and the influences of warp/weft density and yarn fineness on the maximum pore volume in the fabric are analyzed in detail. Based on this model, assume the yarn fineness and warp density is 3 K and 3/cm, respectively, when the weft density increases from 2/cm to 9/cm, and the volume fraction increases from 15% to 35%, the maximum pore volume in the 2D fabric decreases from 2.69 mm 3 to 0.195 mm 3, compared with that in the 2.5D fabric decreases from 2.67 mm 3 to 0.125 mm 3 . At the same volume fraction, the lower the yarn fineness, the smaller the maximum pore volume in 2D and 2.5D fabrics. In addition, when the sum of the warp and weft yarn densities is a certain value, the maximum pore volumes in 2D and 2.5D fabrics decrease as the weft yarn densities increases. Conversely, as the warp density increases, the maximum pore volumes increase.